Oxygen gradient generator to improve in vitro modeling of ischemic stroke - Santiago, João; Kreutzer, Joose; Bossink, Elsbeth; Kallio, Pasi; le Feber, Joost (Frontiers in Neuroscience, 2023)
In the core of a brain infarct, perfusion is severely impeded, and neuronal death occurs within minutes. In the penumbra, an area near the core with more remaining perfusion, cells initially remain viable, but activity is significantly reduced. In principle, the penumbra can be saved if reperfusion is established on time, making it a promising target for treatment. In vitro models with cultured neurons on microelectrode arrays (MEAs) provide a useful tool to investigate how ischemic stroke affects neuronal functioning. These models tend to be uniform, focusing on the isolated penumbra, and typically lack adjacent regions such as a core and unaffected regions (normal perfusion). However, processes in these regions may affect neuronal functioning and survival in the penumbra. Here, we designed, fabricated, and characterized a cytocompatible device that generates an oxygen gradient across in vitro neuronal cultures to expose cells to hypoxia of various depths from near anoxia to near normoxia. This marks a step in the path to mimic core, penumbra, and healthy tissue, and will facilitate better in vitro modeling of ischemic stroke. The generator forms a stable and reproducible gradient within 30 minutes. Oxygen concentrations at the extremes are adjustable in a physiologically relevant range. Application of the generator did not negatively affect electrophysiological recordings or the viability of cultures, thus confirming the cytocompatibility of the device. Thus, the developed device is able to impose an oxygen gradient on neuronal cultures and may enrich in vitro stroke models.